THE DIFFERENCE IN HEIGHT DIFFERENCE BEFORE AND AFTER Zn SUPPLEMENTATION IN STUNTING TODDLERS - Dyah Kusudaryati, Dewi Pertiwi (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
Zn deficiency is associated with growth failure in toddlers. One of the effects of growth failure in toddlers is indicated by the occurrence of stunting (short). The purpose of this research to determine the effect of zinc supplementation on height difference of stunting toddlers. The research design was randomized pretest posttest control group design. The total of thirty six stunting toddlers were divided into two groups. The treatment group received syrup with 20 mg ZnSO4 twice a week for three months whereas the comparison group received placebo without Zn. The results showed that there was no significant difference in height before Zn supplementation between treatment and comparison groups (p = 0,361). There is no significant difference in height after Zn supplementation between treatment and comparison groups (p = 0,613). There was significant difference in height difference before and after Zn supplementation on both of groups (p = 0,000). The conclusions of this study, there is a difference in height difference before and after Zn supplementation in stunting toddlers. Â  Keywords: toddlers, stunting, height, Zn